Endogenous cap reduction in Emission Trading Systems - Thomas Grebel; Rohidul Islam (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2022)
Since its introduction, the European Emissions Trading Scheme (EU ETS) has been struggling with an oversupply of emission allowances and a highly volatile allowance price. One reason for the price decline is technological progress and ist demand-reducing effect, which is only partially taken into account in the system. We propose a simple benchmark approach to endogenously adjust the supply of allowances to technical progress. Using a non-parametric benchmark approach, we measure the required adjustment of the allowance supply to avoid a technologyinduced price decline and to maintain the incentive to invest in low-carbon technologies.
Keywords: 330; EU ETS; emission allowances; Data Envelopment Analysis; endogenous adjustment of supply; technological change; yardstick competition